ANALISIS DAMPAK PROGRAM REHAB RUMAH TIDAK LAYAK HUNI TERHADAP KEMISKINAN DI KABUPATEN SUMBAWA BARAT - HARANI, IKA; UMAR, UMAR; KHADAFIE, MUAMMAR (GANEC SWARA, 2023)
This research discusses the implementation of the Uninhabitable House Rehab program and the effectiveness of the Uninhabitable House Rehab program in reducing poverty levels in West Sumbawa Regency. The aim of this research is to determine the implementation of the Uninhabitable House Rehab program and analyze the effectiveness of the Uninhabitable House Rehab program in reducing poverty levels in West Sumbawa Regency. This research uses mixed methods, qualitative methods to discuss the implementation of the Uninhabitable House Rehab program in West Sumbawa Regency and quantitative methods to analyze the effectiveness of the Uninhabitable House Rehab program in reducing poverty levels in West Sumbawa Regency. The research results show that this program has been implemented well by the West Sumbawa Regency Housing and Settlement Service. The RTLH program in the West Sumbawa community is carried out procedurally in accordance with existing regulations, both from the process of collecting data on aid recipients, mentoring, assessment of aid recipients and monitoring the ongoing rehabilitation process so that the rehabilitation process takes place in accordance with the Budget Plan (RAB). With N = 10, from the t table above we get a t table value of 0.699, the significance value from the table is 0.290 so we get a significance value of 0.290 < 0.699 or the calculated t value < t table so it can be concluded that the House Rehab Program is Unfit for Living (RTLH) effective in reducing poverty in West Sumbawa Regency.